IMPACT OF TYPE-II ENDOLEAK ON ANEURYSM SAC IN A SINGLE CENTER - Varino, Juliana (2017)
Objective: Type 2 endoleak occurs in up to 30% of endovascular aneurysm repair (EVAR), but its long-term significance continues to be one of the most controversial topics. We reviewed our experience to evaluate late outcomes associated with type 2 endoleak. Methods: Between January 2008 to December 2014, 57 patients undergoing EVAR were enrolled in the presenting study. Computed tomography (angioCT) scan assessment was performed to evaluate aneurysm sac evolution. Primary end points included type 2 endoleak incidence, aneurysm sac growth, abdominal aortic aneurysm (AAA) related rupture and death. Secondary endpoints included conversion to open repair, reintervention rate, type 2 endoleak persistence and failure to shrinkage > 5mm and abdominal aortic aneurysm (AAA) rupture. Results: We identified 10 (17.5%) patients with type 2 endoleaks (6 early at the first follow-up CT scan). Median followup was 39.0 ± 31,6 months. Endoleaks persisted in 7 patients (12,2% of total patients; 70,0% of type 2 endoleaks) for >6 months. Overall survival rate was 100%, 98% and 80% at 1, 2 and 5 years. Spontaneous sealing occurred in 6/10 (60%): 3/3 (100.0%) transient type 2 endoleaks and 3/7 (43%) persistent type 2 endoleak. Transient type 2 endoleak (those that resolved <6 months of EVAR) weren´t associated with adverse late outcomes. In contrast, persistent endoleak was associated with several adverse outcomes. When evaluating patients with transitory endoleak vs persistent endoleak, freedom from sac expansion at 1, 3, and 5 years was 100% (transitory) vs 85%, 65%, e 40% (persistent) (P < .001). Patients with persistent endoleak were at increased risk for aneurysm sac growth vs patients without endoleak (odds ratio [OR], 36.0; 95% confidence interval [CI] 2,15 - 79; P < .02). The only reintervention occurred in a persistent endoleak). There was no aneurysm rupture or AAA-related death. Conclusion: Small sample size have limited this study ability to evaluate the impact on endoleak on adverse outcomes. Persistent type II endoleaks led to significant aneurysm sac enlargement, but without increased mortality or rupture rate.